The Role of Sufism Morals in Life - Cinta Yulandari; Raudatul Janah; Maulidya; Eka Maulidini; Ajahari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The role of Sufism in today's life is increasingly important in line with technological advances, fast-paced lifestyles, and increasing stress in society. Sufism, as a spiritual aspect of Islam, offers an approach focused on peace of mind, self-control, and cleansing the heart of negative traits. This study aims to explain how Sufism principles, such as asceticism (zuhud), patience, gratitude, and tawakkul (religious surrender), can be applied in today's context to create a balance between physical and spiritual needs. Through literature research and analysis of ideas, it was discovered that Sufism can be an alternative solution to modern challenges such as mental stress, the crisis of meaning in life, and the decline of morality. Therefore, Sufism serves not only as a spiritual teaching but also as a practical guideline for developing a calmer, more ethical, and more conscious character when facing the challenges of the times.